The Impact of Parental Career-Related Interference on School Burnout: A Mediation Analysis of Career Decision-Making Self-Efficacy - Ardianti, Tanti; Sahin, Arif; Fathurrahman, Farouq; Bangkit, Jean Rala; Rufaidah, Anna; Kiranida, Oktafiana; Nur'aini, Desi (KONSELING RELIGI, 2025)
School burnout characterized by emotional exhaustion, cynicism toward learning, and feelings of incompetence—remains a critical issue in adolescent education, often exacerbated by parental interference in career decision-making. This study examined the direct and indirect effects of parental career-related interference on school burnout, with career decision-making self-efficacy as a mediator. The sample consisted of 383 students from Madrasah Aliyah Negeri (Islamic Senior High Schools) in Bekasi City, Indonesia. Using a quantitative cross-sectional design, data were analyzed through Hayes’ PROCESS Macro Model 4 to test mediation effects. The results revealed that parental career-related interference positively predicted school burnout (β = 0.27, p < 0.05) and career decision-making self-efficacy (β = 0.31, p < 0.05). In turn, career decision-making self-efficacy negatively predicted school burnout (β = –0.19, p < 0.05). The mediation analysis confirmed a significant indirect effect of parental interference on school burnout through self-efficacy (β = –0.060; 95% CI [–0.14, –0.01]). Descriptive statistics showed that the mean scores for school burnout (M = 58.28, SD = 13.93), parental interference (M = 44.83, SD = 6.51), and career decision-making self-efficacy (M = 87.03, SD = 13.27) reflected a relatively consistent response pattern among participants. These findings highlight the contextual nature of parental involvement. In collectivist societies, some forms of parental career-related interference may be viewed as supportive guidance, which can enhance students’ self-efficacy and reduce school burnout. Practical implications for school counseling interventions and strategies to cultivate constructive parental engagement are discussed.